Animal mummies : preserved through the ages - Wilcox, Charlotte (Mankato, Minn. : Capstone High-Interest Books, 2003)
Describes animal mummies, some of the most famous animal mummies and where they have been found, how animals are mummified, how scientists study them, and what they can teach us about the past.
A mammoth discovery -- How animals become mummies -- Animal mummies of Egypt -- Animal mummies in danger.
8 - 14 years
85130
Keywords: Mummified animals; Animal remains (Archaeology); Mummies; Animal remains (Archaeology); Animals